Leachate seepage from landfill: a source of groundwater mercury contamination in South Africa - Nevondo, V; Malehase, T; Daso, AP; Okonkwo, OJ (Water SA, 2019)
Mercury has been used for many centuries in the production of consumer products such as thermometers, electrical switches, fluorescent light bulbs, batteries, biocides and pesticides, cosmetics and dental amalgam filling, among others. After use, these mercury-containing consumer products form part of the municipal solid waste (MSW). As a result of an unseparated solid waste collection system, mercury-containing wastes tend to end up in landfills where mercury and other pollutants can leach out of products into landfill leachates. The present study, therefore, was conducted with the aim of determining the total mercury (THg) concentrations in leachate and sediment samples collected from 4 selected landfill sites (3 sites in Gauteng Province – Soshanguve, Hatherly, Onderstepoort and 1 site in Limpopo Province – Thohoyandou). Groundwater samples were collected from the monitoring boreholes at the four selected landfill sites in the summer and winter periods. An acid digestion method was employed for sample preparation and this was followed by analysis using cold vapour atomic absorption spectrophotometry (CVAAS). The concentration range of total mercury in the Thohoyandou leachate, sediment and groundwater samples was 0.12–2.07 μg/L, 0.03–0.48 μg/g and 0.09–2.12 μg/L, respectively. In Soshanguve, the concentration range of total mercury in leachate, sediment and groundwater samples was 0.10–1.20 μg/L, 0.04–0.62 μg/g and nd –1.66 μg/L respectively, Hatherly concentration range was 0.42–1.31 μg/L and 0.06–0.78 μg/g in leachate and sediment, respectively and in Onderstepoort the concentration range was 0.12–2.41 μg/L, 0.03–0.50 μg/g and 0.05–2.44 μg/L, in leachate, sediment and groundwater, respectively. The findings from this study suggest that there is a likelihood of groundwater pollution by mercury from landfill leachate seepage, particularly for landfills that are not lined with a geomembrane.